Trends in Hepatocellular Carcinoma among Hepatitis C Patients Achieving Sustained Virological Response Following Direct-Acting Antivirals Treatment - Maimunah, Ummi (The Indonesian Journal of Gastroenterology, Hepatology, and Digestive Endoscopy, 2024)
-